Modeling of submarine initial pipe-laying process and its real-time semi-physical virtual reality system. (January 2018) - Xu, Xiujun; Wang, Liquan; Li, Zhen; Yao, Shaoming; Fang, Xiaoming
The mathematical model of the initial pipeline and cable process is created with regard to the ocean current load and wave load; and the mathematical model is solved by the numerical quasi-Newton method to investigate the effects of the current and wave load on the shape and force of the pipeline and cable during the initial pipe-laying process. On this basis, semi-physical simulation system is built to visualize the initial pipe-laying process. The simulation results are compared with OFFPIPE's results to verify the mathematical model. The current and wave load effects on the shape and tension of the pipeline and cable are analyzed. This real-time virtual reality system will help engineering project in risk management and prediction as well as staff training, which is of vital significance for minimizing the risk of the actual pipe laying and improving the efficiency of the pipe-laying work.